2014
DOI: 10.1179/1754762813y.0000000039
|View full text |Cite
|
Sign up to set email alerts
|

Measures of the electrically evoked compound action potential threshold and slope in HiRes 90KTMusers

Abstract: The observed effects of electrode position are consistent with a model in which eCAP threshold is governed primarily by an effect of distance between electrode and neural interface (which is shorter towards the apex of the cochlea) and in which slope is governed primarily by density of surviving neural elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
(43 reference statements)
2
13
0
Order By: Relevance
“…In 89% of the electrodes, the ECAP AGF could be reliably measured. Similarly, Nehme and colleagues (Nehme et al, 2014) measured ECAP AGFs in 34 children and adults using the Advanced Bionics HiRes90K™ device and reported that these measures could be reliability obtained on 91% of the electrodes tested. Data were initially analyzed using several methods to include sigmoidal functions and an area under the curve analysis.…”
Section: Discussionmentioning
confidence: 98%
“…In 89% of the electrodes, the ECAP AGF could be reliably measured. Similarly, Nehme and colleagues (Nehme et al, 2014) measured ECAP AGFs in 34 children and adults using the Advanced Bionics HiRes90K™ device and reported that these measures could be reliability obtained on 91% of the electrodes tested. Data were initially analyzed using several methods to include sigmoidal functions and an area under the curve analysis.…”
Section: Discussionmentioning
confidence: 98%
“…In animal models, several studies demonstrated that the slope of the ECAP AGF is a predictor of the number of remaining nerve fibers or 'neural status' of the ear (Hall, 1990;Pfingst et al, 2015Pfingst et al, , 2017Ramekers et al, 2014). Earlier, it has been proposed that the slope in humans is proportional to the neural density (Cullington, 2003) while the ECAP threshold is affected by the distance between the stimulating electrode and the excitable part of the neurons (Nehmé et al, 2014). A simplified graphical representation of this idea (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…2) illustrates that despite similar distance of electrode to neurons, a lower neural density (a versus b) would result in the same ECAP thresholds but different slopes. The basis for this lies within a model wherein the ECAP amplitude represents the number of responding neurons (Cullington, 2003;Kim et al, 2010;Nehmé et al, 2014). A detailed computer model indicated that the ECAP amplitude does indeed increase with the number of responding neurons but only until certain stimulation amplitudesat very high stimulation intensities, ECAP amplitudes start decreasing again (Briaire and Frijns, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary variable of interest for the eCAP I/O function is the slope because it is positively associated with the density of the surviving neural population, with steeper slopes indicating greater density (e.g. Kim et al, 2010; Nehmé et al, 2014). In addition to the slope, two other parameters are commonly assessed: the lowest stimulation level that can evoke an eCAP (i.e.…”
Section: Introductionmentioning
confidence: 99%